PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN VIDEO INTERATIF TERHADAP KEMAMPUAN BERARGUMENTASI PESERTA DIDIK PADA MATERI GAYA GRAVITASI: indonesia - Ramandha, Tasya; Dadang Gunadi; Poppy Anggraeni (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research is motivated by the low argumentation skills of students, which are marked by not being accustomed to expressing their opinions. One way to improve students' argumentation skills is to use a problem-based learning model assisted by interactive videos. The purpose of this study was to describe the influence of the problem-based learning model assisted by interactive videos on the argumentation skills of grade IV students of SDN Jatihurip, Sumedang Utara District, Sumedang Regency in the 2023/2024 academic year on the material of Gravitational Force. The method used in this study was a pre-experimental type of one group pretest-posttest design. The data collection technique in this study was a test technique consisting of a pretest and posttest. Based on the results of data analysis through the t-test, the t-value is 3.16 ≥ t-table 2.01, so H1 is accepted and Ho is rejected, meaning that there is a significant difference in pretest and posttest values ​​from the application of the interactive video-assisted problem-based learning model on the argumentation skills of grade IV students of SDN Jatihurip, Sumedang Utara District, Sumedang Regency in the 2023/2024 Academic Year on the material of gravitational force. Thus, it can be concluded that the use of the interactive video-assisted problem-based learning model has a significant effect on the argumentation skills of grade IV students of SDN Jatihurip, Sumedang Utara District, Sumedang Regency in the 2023/2024 Academic Year on the material of gravitational force.